Gender Variation in Voice Quality in Learning English as A foreign Language: An Investigation into Libyan Learners’ Perceptions (مجلة البحوث الأكاديمية, 2019)
This study was carried out to investigate the contribution of gender in voice quality in the production of English as a foreign language according to the opinions of first and second semester students, at the Department of English, Faculty of Arts in Misurata University. The problem of this study was centralized in a number of voice quality aspects including: loudness, pitch, sharpness, nasality, harshness, creakiness, whisper, and speed. A questionnaire with ten statements was floated to 82 students to find out the effect of gender variation on voice quality in learning the target language i.e. English. The collected data was analyzed quantitatively. Moreover, the participants’ perceptions were categorized based on their gender. The study concluded that students’ perceptions were mostly positive regarding that matter. According to the study results, it can be observed that how both male and female participants showed a high tendency of agreeing to most of the points assigned to the questionnaire, which proves that students generally believe that male and female speakers of English as a foreign language differ in voice quality when producing the language in an EFL context.
Keywords: gender variation; voice qualities; loudness, pitch, sharpness; speed